FORMULATION OF TECHNICAL FILES AND PUBLIC INVESTMENT PROJECTS IN A MUNICIPALITY OF LA LIBERTAD - Tocto Cabanillas, Samuel (2023)
This article seeks to examine the relationship between the formulation or preparation of technical files and the investment projects of the municipality of Sartimbamba, located in Sánchez Carrión, La Libertad. To investigate these connections, the cost and execution time of 104 projects in the municipality of Sartimbamba were evaluated. The main findings reveal a moderate positive connection between the formulation or preparation of technical files and the quality of the investment projects of the municipality of Sartimbamba in 2021, with a conversion coefficient of 0.674, according to Spearman's Rho method. Therefore, it is observed that the formulation or elaboration of the technical files plays a significant role in the construction stage of the projects of the municipality of Sartimbamba. In other words, the better the technical files are prepared or formulated, the lower the incidence of setbacks during the construction process of the works.